On Angels and Devils and Stages Between Book review - Jackson, Paul R. W. (Dance Books Ltd., Alton,Hampshire (UK), 1999)
Contemporary lives in contemporary dance. This volume by David Wood is a trifle coy in the sense that it cannot decide if it is an autobiography o not.
On Angels and Devils and Stages Between. David Wood, Harwood Academic Press, 1999.